A Secondary Analysis of Peer Support and Family Acceptance Among Homosexual Living with HIV and Antiretroviral Therapy: Quality of Life Perspectives - Ina Martiana; Agung Waluyo; Sri Yona; Edianto Edianto (Jurnal Keperawatan Indonesia, 2021)
Men who have sex with men (MSM) comprise a population at risk for HIV infection. Assessing the Quality of Life (QOL) in MSM might be different than other populations. This study showed a secondary analysis from our previous research. It was needed to understand whether peer support and family acceptance had an impact on QOL of MSM living with HIV and ART (Antiretroviral Therapy). A total of 175 respondents were involved in this cross-sectional study that was carried out with purposive sampling. The questionnaires were translated to Bahasa and tested for validity and reliability. Data questionnaires completed were analyzed. Results showed that peer support was positively correlated with QOL (p= 0.023; OR= 2.070), and also, family acceptance was significantly related to QOL (p= 0.001; OR= 2.766). Thus, peer support and family acceptance are important factors affecting the well-being and QOL of MSM living with HIV and ART. This finding can be used for the improvement of QOL in people living with HIV. Abstrak Dukungan Sebaya dan Penerimaan Keluarga terhadap Kualitas Hidup Homoseksual dengan HIV dan Terapi Antiretroviral. Laki-laki yang berhubungan seks dengan laki-laki (LSL) merupakan populasi yang berisiko terinfeksi HIV. Menilai kualitas hidup (QOL) pada LSL mungkin berbeda dari populasi lainnya. Penelitian ini merupakan analisis sekunder dari penelitian sebelumnya. Kami menguji apakah dukungan sebaya dan penerimaan keluarga berdampak pada kualitas hidup pada LSL dengan HIV dan ART (terapi antiretroviral). Sebanyak 175 responden dilibatkan dalam studi cross-sectional yang dilakukan melalui purposive sampling. Data kuesioner yang sudah terisi komplit, akan dilakukan analisa. Hasil penelitian menunjukkan bahwa dukungan sebaya berhubungan positif dengan kualitas hidup (p= 0,023; OR= 2,070) dan juga penerimaan keluarga secara signifikan berhubungan dengan kualitas hidup (p= 0,001; OR= 2,766). Dengan demikian, dukungan sebaya dan penerimaan keluarga merupakan variabel penting yang mempengaruhi kesejahteraan dan kualitas hidup LSL yang hidup dengan HIV dan ART. Temuan ini dapat digunakan untuk peningkatan QOL pada orang dengan HIV. Kata Kunci: dukungan sebaya, HIV, kualitas hidup, penerimaan keluarga